2020
DOI: 10.1186/s40359-020-00426-0
|View full text |Cite
|
Sign up to set email alerts
|

Family Club Denmark #strongertogether - a volunteer intervention for disadvantaged families: study protocol for a quasi-experimental trial

Abstract: Background Need-oriented family support programs are examples of voluntary-based interventions increasingly recognized by the public sector as an important contribution to health and social care provision. Voluntary interventions are attractive because of their focus on activism, inclusion, and participation, but also their low cost and easy accessibility. There is an increasing demand for documentation of the effectiveness of family support programs. Methodologically sound studies are, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…We conducted this study according to CONSORT guidelines [ 42 , 43 ]. More details about this study can be found in the study protocol [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted this study according to CONSORT guidelines [ 42 , 43 ]. More details about this study can be found in the study protocol [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the timing of the administration of measures. More details about the measures are described in the study protocol [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation